2022
DOI: 10.3389/fmed.2022.830853
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Surface Ion-Channels Are Closely Related to Dry Eye: Key Research Focus on Innovative Drugs for Dry Eye

Abstract: Abundant ion-channels, including various perceptual receptors, chloride channels, purinergic receptor channels, and water channels that exist on the ocular surface, play an important role in the pathogenesis of dry eye. Channel-targeting activators or inhibitor compounds, which have shown positive effects in in vivo and in vitro experiments, have become the focus of the dry eye drug research and development, and individual compounds have been applied in clinical experimental treatment. This review summarized v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 102 publications
0
28
0
Order By: Relevance
“…Morphological changes measured with corneal confocal microscopy may not reflect corneal nerve neurophysiological abnormalities, which may play a predominant role in dry eye disease. 34,45 Furthermore, studies have shown that ocular surface inflammation or loss of homeostasis can induce neuropeptide production and secretion in large-sized trigeminal ganglion ocular surface neurons, supporting dysfunctional corneal nociceptors and not corneal nerve fiber loss as the mediator of dry eye disease in these two diabetes groups. 37,46 Also, nerve excitability studies have shown abnormalities in nerve conduction in type 2 diabetes mellitus with or without chronic kidney disease, suggesting the potential of corneal nerve dysfunction instead of nerve fiber loss as the driver of dry eye disease in type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Morphological changes measured with corneal confocal microscopy may not reflect corneal nerve neurophysiological abnormalities, which may play a predominant role in dry eye disease. 34,45 Furthermore, studies have shown that ocular surface inflammation or loss of homeostasis can induce neuropeptide production and secretion in large-sized trigeminal ganglion ocular surface neurons, supporting dysfunctional corneal nociceptors and not corneal nerve fiber loss as the mediator of dry eye disease in these two diabetes groups. 37,46 Also, nerve excitability studies have shown abnormalities in nerve conduction in type 2 diabetes mellitus with or without chronic kidney disease, suggesting the potential of corneal nerve dysfunction instead of nerve fiber loss as the driver of dry eye disease in type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…Our study used corneal confocal microscopy, which provides corneal nerve morphological parameters rather than cornea neurophysiological measures such as nerve excitability. Morphological changes measured with corneal confocal microscopy may not reflect corneal nerve neurophysiological abnormalities, which may play a predominant role in dry eye disease 34,45 . Furthermore, studies have shown that ocular surface inflammation or loss of homeostasis can induce neuropeptide production and secretion in large-sized trigeminal ganglion ocular surface neurons, supporting dysfunctional corneal nociceptors and not corneal nerve fiber loss as the mediator of dry eye disease in these two diabetes groups 37,46 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, the most important method for treating DED is using artifcial tears locally to improve ocular surface humidity and lubrication capacity [38,39]. Some topical drugs are approved for treating DED with anti-infammatory and immunomodulatory efects, such as Cyclosporin A [40], corticosteroids [41], as well as emerging therapeutics such as lacrimal and diquafosol sodium [42][43][44][45][46]. Also, there are still challenges in the treatment of DED [47].…”
Section: Discussionmentioning
confidence: 99%